2021
DOI: 10.1177/03015742211015934
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Growth Pattern and Palatal Rugae Pattern in South Indian Population

Abstract: Aim: To determine the correlation between palatal rugae (PR) pattern and subjects with vertical, average, and horizontal growth pattern and to determine gender variation if any. Material and Methods: One hundred and twenty study models were divided into horizontal, vertical, and average growth patterns with 40 (20 males and 20 females) samples in each group. The pattern of PR was assessed in each group using a template. Result: Type B (wavy type) PR occurs more often in horizontal and average growth pattern (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One study that compared class II division I with class I rugae pattern was by Gandikota et al [12] STUDIES ON VERTICAL DIMENSION Solarte et al, Sudhakar et al, Maria E. Saadeh et al are three studies which compared the relationship between palatal rugae & vertical dimension. [11,14,24]…”
Section: Studies On Direction Of Palatal Rugaementioning
confidence: 99%
See 2 more Smart Citations
“…One study that compared class II division I with class I rugae pattern was by Gandikota et al [12] STUDIES ON VERTICAL DIMENSION Solarte et al, Sudhakar et al, Maria E. Saadeh et al are three studies which compared the relationship between palatal rugae & vertical dimension. [11,14,24]…”
Section: Studies On Direction Of Palatal Rugaementioning
confidence: 99%
“…[20] There were contradictory results found with regards to the association between sagittal malocclusion and rugae patterns and found no statistically significant difference among different malocclusion about rugae pattern [12,[14][15][20][21] whereas few studies reported that the primary, secondary as well as the fragmentary rugae were greater in class II malocclusion and has significant difference in rugae pattern with class II malocclusion than class I and class III. [13,[18][19]24] One study that compared rugae pattern in class I and class II division I, where the length of second and third rugae were used and found that the length of rugae was shorter in class II division 1 than class I and concluded that there was a notable constriction of rugae observed in class II division I than in class I. [11] VERTICAL ASPECT With regard to the direction, rugae were horizontally oriented with parallel distribution among skeletal open bite cases.…”
Section: Sagittal Aspectmentioning
confidence: 99%
See 1 more Smart Citation